The Organization of Non-Formal Education at the PKBM Tunas Aksara Institution in Kuripan, West Lombok District - Nasrudin; A. Hari Witono; Fahruddin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the organization of non-formal education at the PKBM Tunas Aksara Kuripan Institute, West Lombok Regency. This study uses a qualitative approach and method of data sources in the form of sources from the Head of the Institution, the person in charge of the program, the Principal, the Teacher, the Committee and relevant documents. Data collection techniques through interviews, observation, and documentation. The results showed that the implementation of non-formal education in planning, organizing, implementing and evaluating was good enough. Planning is done systematically by applying allocative planning. Organizing is based on the responsibility and authority of each part that has been determined by its job description. Program implementation runs according to the plan and objectives that have been determined. The main programs held are equivalency, early childhood education, literacy and PKW. Evaluation focuses on learning implementation